Customer Satisfaction Measurement - American Productivity & Quality Center; American Productivity & Quality Center (APQC American Productivity & Quality Center, 1996)
Learn how best-practice organizations share ways to develop and implement improved customer satisfaction measurement (CSM) processes that link to broader quality-related processes and corporate mission statements in Customer Satisfaction Measurement. Discover strategic issues, CSM implementation, organizational issues, CSM methodology, and links from CSM to business results and processes. Examine other emerging trends from the study data, including cost-benefit analysis, customer value, organizational buy-in, and employee performance and business results.